(untitled) (Lex localis - Journal of Local Self-Government, 2024)
Local government units (LGUs) in the Philippines are under pressure to deliver faster, more transparent, and citizen-responsive services under constrained fiscal and human-resource conditions. Artificial intelligence (AI) has been promoted internationally as a tool for administrative automation, decision support, and citizen-facing service interfaces, yet empirical evidence on feasibility in non-metropolitan LGUs remains limited. This study examines the applicability of AI in LGUs in the Zamboanga Peninsula (Region IX), Philippines. Using a mixed-methods design, the research integrates a survey of LGU employees (n=200), key informant interviews (n=10), and focus group discussions (10 groups) to assess current adoption patterns, perceived benefits, readiness conditions, and barriers. Findings suggest that AI adoption is emerging but uneven. Reported use is largely concentrated in back-office functions such as data processing, document management, and basic analytics, with limited deployment in higher-risk applications such as predictive analytics and automated citizen engagement. Participants perceive potential gains in operational efficiency, data-driven decision making, and service accessibility, but emphasize persistent constraints in data infrastructure, digital skills, procurement and financing, and governance safeguards related to privacy, cybersecurity, and accountability. The paper proposes a staged implementation pathway for Region IX LGUs that prioritizes data governance foundations, capacity development, and responsible AI controls before scaling complex use-cases, and recommends regional partnerships with universities and technology providers to address capability gaps and reduce duplication across LGUs.